Only the guilty survive : a thriller - Robards, Kate (Crooked Lane Books, 2024)
"A podcaster digs into strange connections between a cult's mass suicide and the murder of a local beauty queen in this twisty psychological thriller about true crime culture, perfect for fans of Riley Sager and Lisa Jewell. The mass suicide of a cult known as the Flock sent shockwaves through the small rural town of Iola, Michigan. Led by the charismatic Dominic Bragg, the Flock camped at an abandoned bird sanctuary before their sudden and shocking demise. The deaths came just weeks after one of their members, Laurel Tai, a local pageant queen, was abducted. The town turned its blame and fear onto the sole survivor, Claire Kettler-Laurel's best friend. Burdened by grief and unanswered questions about her friend's murder and her fellow cult members' deaths, Claire can't help but wonder what really happened, especially when the cult leader is nowhere to be found. When podcaster Arlo Stone begins poking around ten years later, determined to uncover the truth about the cult and Laurel's murder, Claire is propelled back into action. In a desperate attempt to puzzle out the past and keep her secrets from being spilled for the entertainment of thousands of listeners, Claire must dig into a tangle of unanswered questions before time runs out and history repeats itself."--